Partitioning autotrophic and heterotrophic respiration in an ombrotrophic bog - Rankin, Tracy; Roulet, Nigel; Humphreys, Elyn; Peichl, Matthias; Jӓrveoja, Jӓrvi (Frontiers in Earth Science, 2023)
Northern peatlands are globally significant carbon stores, but the sink strength varies from year to year due to changes in environmental conditions. Ecosystem respiration (ER) is composed of both autotrophic respiration (AR) that consists of respiration by plant parts, and heterotrophic respiration (HR) that consists of respiration by microbial bacteria in the soil, fungi, etc. Manual measurements only crudely partition AR and HR, which may lead to erroneous estimates if a change favours one form of respiration over another and may influence our interpretation in the magnitude of respiration. HR has also been thought to be more linked to vegetation dynamics, particularly in wetter, sedge-dominated ecosystems like fens. It is unknown whether such plant-soil-root interactions influence HR in peatlands dominated by woody shrubs whose water table is located further below the surface. The objectives of this study were to 1) determine the contributions of AR and HR at Mer Bleue, an ombrotrophic bog, 2) explore how environmental conditions influence ER and its components, 3) determine how different methodological approaches (e.g. directly measured respiration using automatic chambers vs. extrapolated calculations) can influence our interpretation in the magnitude of respiration, and 4) compare the respiration dynamics with those found in the literature for other peatland types. Our results revealed differences in AR and HR contributions to ER compared to other peatland types reported in the literature. The AR/HR ratio was 3.0 and AR contributions to ER were ~ 75% at our study bog, which is generally higher than AR contributions from fens, but also decreased substantially during extended drier periods. HR contributions increased with rising temperature and water table depth. Directly measured ER was smaller than when ER was estimated using night-time relationships with temperature. The magnitude of ER changed depending on the plant biomass, which we believe to be a result of vegetation dynamics influencing HR. The results of this study improved our understanding of peatland carbon cycling as well as the conceptualization of HR.